Indoleamine 2,3-dioxygenase 1 limits hepatic inflammatory cells recruitment and promotes bile duct ligation-induced liver fibrosis - Mo, Chan (Cell Death Dis, 2021)
Liver fibrosis is a course of chronic liver dysfunction, can develop into cirrhosis and hepatocellular carcinoma. Inflammatory insult owing to pathogenic factors plays a crucial role in the pathogenesis of liver fibrosis. Indoleamine 2,3-dioxygenase 1 (IDO1) can affect the infiltration of immune cells in many pathology processes of diseases, but its role in liver fibrosis has not been elucidated completely. Here, the markedly elevated protein IDO1 in livers was identified, and dendritic cells (DCs) immune-phenotypes were significantly altered after BDL challenge. A distinct hepatic population of CD11c(+)DCs was decreased and presented an immature immune-phenotype, reflected by lower expression levels of co-stimulatory molecules (CD40, MHCII). Frequencies of CD11c(+)CD80(+), CD11c(+)CD86(+), CD11c(+)MHCII(+), and CD11c(+)CD40(+) cells in splenic leukocytes were reduced significantly. Notably, IDO1 overexpression inhibited hepatic, splenic CD11c(+)DCs maturation, mature DCs-mediated T-cell proliferation and worsened liver fibrosis, whereas above pathological phenomena were reversed in IDO1(−/−) mice. Our data demonstrate that IDO1 affects the process of immune cells recruitment via inhibiting DCs maturation and subsequent T cells proliferation, resulting in the promotion of hepatic fibrosis. Thus, amelioration of immune responses in hepatic and splenic microenvironment by targeting IDO1 might be essential for the therapeutic effects on liver fibrosis.